(untitled) - Lindberg, David C. (Chicago, 1992)
This landmark book represents the first attempt in two decades to survey the science of the ancient world, the first attempt in four decades to write a comprehensive history of medieval science, and the first attempt ever to present a full, unified account of both ancient and medieval science in a single volume. In The Beginnings of Western Science, David C. Lindberg provides a rich chronicle of the development of scientific ideas, practices, and institutions from the pre-Socratic Greek philosophers to the late-medieval scholastics.
Keywords: Science, Ancient,Science, Medieval,Khoa học, cổ đại,Khoa học, Trung đại; History,History,Lịch sử,Lịch sử